Effect of Antihypertensive Therapy Compliance Using Medication Possession Ratio Method on Blood Pressure in Patients with Hypertension - Afriani Ireineldis Anugera; Christianus Heru Setiawan (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2022)
Hypertension is a circulatory system disorder that causes an increase in blood pressure, specifically systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg. Hypertension can cause serious medical conditions such as damage to various organs. The complications caused by hypertension can be prevented with treatment regularly to achieve controlled blood pressure. This study determines the relationship between antihypertensive therapy compliance to blood pressure in hypertensive patients. This type of research is analytical observational with retrospective cohort design and purposive sampling techniques. The data were obtained from patients’ medical records, including demographic data, blood pressure, and prescribed drugs. The subject's compliance was measured using the Medication Possession Ratio (MPR). A total of 124 subjects met the inclusion criteria. The data were analyzed using a chi-square test with Yates correction. Most patients had uncontrolled blood pressure as much as 101 patients. The statistical analyses show that antihypertensive therapy compliance affects controlled blood pressure in patients with hypertension (p= 0.00). More efforts to support adherence to hypertensive treatment should be initiated to have greater effect on therapy compliance.